A meta-analysis of closed reduction percutaneous pinning and open reduction with pin fixation of pediatric humeral lateral condylar fracture - Meng, Chao; Meng, Zhen; Huang, Xin; Zhao, Fenghua; Yang, Qun (Frontiers in Pediatrics, 2023)
Objective: To compare the effectiveness and safety of closed reduction percutaneous pinning versus open reduction with pin fixation to treat the pediatric humeral lateral condylar fracture. Methods: Studies comparing closed reduction percutaneous pinning vs. open reduction with pin fixation for treating pediatric lateral humeral condyle fractures were found by searching Pubmed, Embase, the Cochrane Library, and Web of Science databases, including randomized/non-randomized controlled, retrospective case-control, and prospective cohort studies. Furthermore, quality evaluation and data retrieval were conducted after the literature review. A meta-analysis was performed using RevMan 5.4 software to compare both groups' outcome measures. Results: This Meta-analysis incorporated eight studies with 856 cases. The Meta-analysis found no significant difference in functional outcomes, superficial infection, deep infection, poor fracture union, avascular necrosis of the humeral capitulum, or lateral spur formation between groups. However, the status of unaesthetic scars in the CRPP group was superior. Conclusions: For pediatric humeral lateral condylar fracture surgical therapy, the efficacy and safety of closed reduction percutaneous pinning vs. open reduction with pin fixation were not significantly different; closed reduction percutaneous pinning offered the benefit of eliminating unaesthetic scar. However, further high-quality research is required to verify the conclusions of this Meta-analysis.